Selective influence of Sox2 on POU transcription factor binding in embryonic and neural stem cells. (September 2015) - Mistri, Tapan Kumar; Devasia, Arun George; Chu, Lee Thean; Ng, Wei Ping; Halbritter, Florian; Colby, Douglas; Martynoga, Ben; Tomlinson, Simon R; Chambers, Ian; Robson, Paul; Wohland, Thorsten
Abstract Embryonic stem cell (ESC) identity is orchestrated by co‐operativity between the transcription factors (TFs) Sox2 and the class V POU‐TF Oct4 at composite Sox/Oct motifs. Neural stem cells (NSCs) lack Oct4 but express Sox2 and class III POU‐TFs Oct6, Brn1 and Brn2. This raises the question of how Sox2 interacts with POU‐TFs to transcriptionally specify ESCs versus NSCs. Here, we show that Oct4 alone binds the Sox/Oct motif and the octamer‐containing palindromic MORE equally well. Sox2 binding selectively increases the affinity of Oct4 for the Sox/Oct motif. In contrast, Oct6 binds preferentially to MORE and is unaffected by Sox2. ChIP‐Seq in NSCs shows the MORE to be the most enriched motif for class III POU‐TFs, including MORE subtypes, and that the Sox/Oct motif is not enriched. These results suggest that in NSCs, co‐operativity between Sox2 and class III POU‐TFs may not occur and that POU‐TF‐driven transcription uses predominantly the MORE cis architecture. Thus, distinct interactions between Sox2 and POU‐TF subclasses distinguish pluripotent ESCs from multipotent NSCs, providing molecular insight into how Oct4 alone can convert NSCs to pluripotency.